내도복 보리호위축병저항성 겉보리 ‘다혜’ - 김양길(Yang-Kil Kim); 백성범(Seong-Bum Baek); 이미자(Mi-Ja Lee); 김미정(Mi-Jung Kim); 김홍식(Hong-Sik Kim); 현종내(Jong-Nae Hyun); 황종진(Jong-Jin Hwang); 서세정(Sae-Jung Suh); 김시주(Si-Ju Kim); 김재철(Jae-Chul Kim); 정재현(Jai-Hyun Jeung) (Korean journal of breeding, 2013)
‘다혜’는 답리작 적응 조숙 내재해 다수성 등을 목표로 조 숙 대립 특성을 지닌 ‘수원318호’를 모본으로, 보리호위축병 에 강한 ‘수원311호’를 부본으로 인공교배 육성 선발된 ‘익산 409호이다. 파성은 Ⅲ형이며, 이삭의 밀도가 조밀한 편이며 까락이 길지만 탈망성이 좋다. 출수기와 성숙기는 각각 4일 빠른 조숙종이다. 흰가루병은 ‘올보리’와 비슷하며, 보리호위 축병에 대한 저항성을 나타냈다. 내한성과 내도복성은 ‘올보 리’보다 다소 강하였다. 간장(88 cm)과 수장은 ‘올보리’와 비 슷하였으며, m 2당 수수는 666개로 ‘올보리’보다 7개 적고, 1 수립수는 52개로 2개 많으나 통계적인 차이는 없었다. 천립 중은 ‘올보리’와 비슷한 대립종이며, 1 L중은 다소 가벼웠다. 단백질 함량, β-glucan 함량과 정맥률은 비슷하였고, 입백도 는 약간 높았다. 엿기름의 효소력가는 ‘올보리’보다 25 DP 높았다. 수량은 전작에서 4.00 MT/ha, 답리작에서 4.11 MT/ha 이었다. ‘Dahye’, a new covered cultivar derived from the crosses between ‘Suwon318’ and‘Suwon311’ developed at the Honam Agricultural Research Institute (HARI), NICS, RDA in 2007. The initial crossing was made in 1996 and an elite line, ‘SB964008-B-B-B-92’ was selected from under yield trial test in 2004. It was designed as ‘Iksan409’ and showed a high yield and had good quality in the regional yield trials (RYT) from 2005 to 2007. It was released with the name of ‘Dahye’.‘Dahye’had a rate Ⅲ growth habit, green leaf and stem, compact spike and long rough awns. The heading date was April 29 in upland and April 20 in paddy field, which was 2 and 5 days earlier than that of check cultivar,‘Olbori’, respectively. It had 88 cm of culm length, 4.2 cm of spike length and 666 spikes per m2, 52 grains per spike, 35.6 g of 1,000-grain weight and 702 g of test weight. It showed stronger winter hardiness and higher resistance to barley yellow mosaic virus (BaYMV) than those of check cultivar. It had similar protein content with check cultivar and higher whiteness and diastatic power (DP) than those of Olbori. The average yield of the pearled grain in the regional yield trial (RYT) was 4.00 ton ha-1 in upland and 4.11 ton ha-1 in paddy field. This cultivar would be suitable for the area that the daily minimum mean temperature is above -8℃ in January in Korean peninsula.